2019
DOI: 10.1002/iub.2049
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of vildagliptin on TNF‐α‐induced chondrocyte senescence

Abstract: Osteoarthritis (OA) is a common age‐related disorder. Chondrocytes in joint tissue play a critical role in normal articular cartilage function and tissue homeostasis. Local inflammatory cytokine‐induced chondrocyte senescence contributes to the development and progression of OA. Various dipeptidyl peptidase‐4 (DPP‐4) inhibitors have been widely used to treat type 2 diabetes. Here, we report a novel pharmacological role of the DPP‐4 inhibitor vildagliptin in chondrocyte senescence. Our data indicate that DPP‐4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 30 publications
(28 reference statements)
4
20
0
Order By: Relevance
“…The cell surface expression of DPP4 makes it a promising candidate for targeted treatment of senescent cells through antibody-dependent cell-mediated cytotoxicity [ 8 ]. Treatment of senescence-related chronic disease, as shown by recent studies with DPP4 inhibitors that ameliorated atherosclerosis in type 2 DM patients [ 30 , 31 ], prevented vascular aging [ 32 ] and protected chondrocytes from TNF- α -induced senescence [ 33 ]. We noticed increased SIRT1 in association with DPP4 reduction upon CBX4 activation of WI-38 cells.…”
Section: Discussionmentioning
confidence: 99%
“…The cell surface expression of DPP4 makes it a promising candidate for targeted treatment of senescent cells through antibody-dependent cell-mediated cytotoxicity [ 8 ]. Treatment of senescence-related chronic disease, as shown by recent studies with DPP4 inhibitors that ameliorated atherosclerosis in type 2 DM patients [ 30 , 31 ], prevented vascular aging [ 32 ] and protected chondrocytes from TNF- α -induced senescence [ 33 ]. We noticed increased SIRT1 in association with DPP4 reduction upon CBX4 activation of WI-38 cells.…”
Section: Discussionmentioning
confidence: 99%
“…After stimulation, the cell cycle of chondrocytes was analyzed using flow cytometry. Briefly, after fixation with ethanol, cells were permeabilized with 0.1% Triton X-100 and stained with propidium iodide [18]. The patterns of cell cycles were counted via flow cytometry.…”
Section: Flow Cytometrymentioning
confidence: 99%
“…However, gliptins can bind to DPP4 in a region in close proximity with the SLIG aminoacids sequence and may thus hamper the direct interaction between sDPP4 and PAR2 in endothelial cells. 52 Interestingly, it was reported that linagliptin treatment ameliorates the progression of premature aging phenotype in klotho KO (knockout) mice-a model of premature aging. 53 Besides, obese mice treated with DPP4 inhibitors exhibited greater survival and life span.…”
Section: Discussionmentioning
confidence: 99%